Jellyfish biodiversity and human-jellyfish conflict in Sabah, Malaysia - Chuan Chee Hoe (2023)
Medusozoan jellyfish (Cnidaria) represent an important part of the ocean’s ecosystem, and despite their wide-ranging impacts to human activities, relatively little knowledge is currently present on their population within the state of Sabah. In order to determine the species biodiversity and the impact that these jellyfish have to human health in the state, an assessment of jellyfish biodiversity was carried out. First, a literature review of jellyfish reports within the bodies of water surrounding Borneo from 1870-1970 was carried out in order to ascertain the potential species which may occur in Sabah waters. Next, the current biodiversity of jellyfish in the state was determined via the opportunistic sampling of jellyfish throughout February to April 2018 and 2020. Collected jellyfish samples were preserved at 7°C in 4% buffered formalin in seawater, and re-examination of previously unidentified jellyfish records was used to create an up-to-date collection of jellyfish species in the state. Finally, a record of serious and fatal jellyfish sting cases from 1991 to 2021 was also produced through reviewing reports in media, scientific literature, and reports from the medical sector. Historical records from 1870-1970 show that 162 species of jellyfish (99 hydrozoans, 57 scyphozoans and six cubozoans) were previously recorded in the study area. Next, the current jellyfish biodiversity of the state was expanded by new records of 11 species in addition to three unidentified species which had hitherto not been reported from the state. These jellyfish consist of three hydrozoan species, ten scyphozoan species and one cubozoan species, and their records expand the total number of species in the state to 25 in total. The large difference between the number of jellyfish species recorded in the present day compared to that in historical records suggest that the current records of jellyfish biodiversity in the state is highly underestimated, especially in the classes Hydrozoa and Cubozoa. Since 1991, there have been 36 cases of serious jellyfish envenomation in the state, with six resulting in fatality of the sting victim. Children are most at risk of developing serious symptoms. Cases of jellyfish stings were reported from all parts of the state. Sting events are more common from November to January; however, stings were reported year-round. Among the species known to occur in the state is the deadly box jellyfish Chironex yamaguchii Lewis & Bentlage, 2009, which has been implicated in multiple serious jellyfish stings and fatalities. Through this study, a list of jellyfish species which could occur in the state has been produced, as well as a checklist of jellyfish species currently known to occur within the state, with physical samples collected deposited for future reference. It was also found that harmful jellyfish pose a threat to coastal human populations throughout the state. More research on jellyfish needs to be prioritized, not only to determine the true biodiversity of jellyfish in the region and to identify and prepare for harmful jellyfish species, but also to raise public awareness of jellyfish-related risks and proper safety-seeking attitude in order to reduce the risk of jellyfish-human conflicts.